RI 3330 Engineering Report On Oklahoma City Oil Field, Oklahoma ? Introduction (204656e0-85df-437b-a9d9-8b83d17b6558) - H. B. Hill (The National Institute for Occupational Safety and Health (NIOSH), 1936)
Virtually from the date of its discovery in December 1928 the Oklahoma City oil and gas field, Oklahoma County, Okla., has attracted national and international attention. The history of the field has been associated closely with rules and regulations pertaining to production control and proration practices. Early development was rapid, and Oklahoma City soon attained the distinction of being the first major field in which the producing wells were over a mile in depth. Before the structural features of the reservoir had been disclosed every outpost well was considered a "wildcat", so complex appeared the underground geology. The wells not only were deep and the reservoir pressures high, but the production from the early wells was a high A.P.I. gravity oil, accompanied by large volumes of gas. Several "blow-outs" and fired occurred during the early development, and the close proximity of these now unusual events to a large city gave the field much publicity, both local and national. Later, when its production threatened to demoralize the market for oil and its products, the Oklahoma. City field again attracted wide publicity. The then little understood geology of the underground reservoir and the diversity of ownership of the land overlying the producing structure made orderly development and production difficult to enforce. Proration was enforced with difficulty, and the rate of production from the field continued to increase until, on August 4, 1931, martial law was declared in all prorated fields of the State, and most of the wells in the Oklahoma City field wore shut in. On October 9, 1931, permission was granted to reopen and produce the wells in the Oklahoma City field. The order permitting production of the wells provided that during the period beginning October 10 and extending to October 20, 1931, all wells in the field that had not produced more oil than specified under the earlier proration orders and that had been shut in for the required 65-day period were permitted to produce 5 percent of their last potential during that 10-day period.